Assessing the Potential Impact of General Collective Intelligence - Williams, Andy (My University, 2020)
The concept of General Collective Intelligence or GCI is summarized, and the potential for GCI to exponentially increase the general problem-solving ability of the group so that it is far larger than that of any individual in the group, and therefore the potential for GCI to exponentially increase the ability of groups to impact collective outcomes are explored. GCI is represented as a repeating pattern, beginning with a first order GCI, then progressing to an Nth order one, where N might be limited by the resources available, and where each order is suggested to create the potential for an exponential increase in general problem-solving ability. Finally, the claim that such an exponential increase in potential for impact on any general problem makes GCI the most important innovation in human history, and the most important innovation in the near term future, until the transition to second order GCI, is explored
Keywords: General Collective Intelligence; Collective Intelligence; general problem solving ability; c factor